Pengaruh Input Data Penjualan dan Pemahaman Karyawan tentang Penggunaan Aplikasi Accurate terhadap Pengelolaan Manajemen pada Perusahaan Depo Lakban Surabaya - Ananda Nurhadi Syaifulloh; Iswati Iswati; Anis Fitriyasari; Arief Widjadmoko (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study aims to analyze the impact of the Accurate application on the efficiency of sales data input at Depo Lakban Surabaya. The research method used is quantitative with a questionnaire as the data collection instrument. The validity test results show that all statement items are valid, with correlation values greater than the critical value. The instrument's reliability was tested using Cronbach's Alpha, which showed a value of 0.945 > 0.600, indicating that the instrument is reliable. The normality test showed that the data is normally distributed with a significance value of 0.143 > 0.05. The regression results show that the Accurate application (X1) has a coefficient of 0.364 with a significance value of 0.005 < 0.05, while another factor (X2) has a coefficient of 0.673 with a significance value of 0.003 < 0.05. The obtained regression equation is Y = 0.901 + 0.364X1 + 0.673X2. The t-test and F-test show that both independent variables significantly influence the efficiency of sales data input. This research concludes that the use of the Accurate application has an influence on the management of sales data input at the Surabaya Lakban Depo Company. And the understanding of Depo Lakban Surabaya employees also influences the company's management.